2022
DOI: 10.1002/jbt.23257
|View full text |Cite
|
Sign up to set email alerts
|

The effects of boron‐supplemented diets on adipogenesis‐related gene expressions, anti‐inflammatory, and antioxidative response in high‐fat fed rats

Abstract: The fatty liver syndrome caused by nutritional factors is a common cause of hepatic dysfunction globally. This research was designed to study the shielding effect of boron in rats fed a diet having high fat. Overall, 40 Wistar albino male rats were placed into one control and four treatment groups, that is, each having eight rats. Group I was provided with a standard rat diet while group II was only provided a high‐fat diet for 60 days. Groups III, IV, and V were provided with 5, 10, and 20 mg/kg/day boron, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
2
2
1
Order By: Relevance
“…In the present study, SPP and BA supplementation increased PPARγ and decreased SREBP-1c, LxR-α, and FAS expression in the liver of rats. These data are consistent with earlier reports showing the effects of boron on lipid metabolism-related genes [ 21 , 39 ]. For example, Kucukkurt et al showed that 10 mg/kg B (as BA) increased PPARγ expression in the liver in HFD-fed rats [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, SPP and BA supplementation increased PPARγ and decreased SREBP-1c, LxR-α, and FAS expression in the liver of rats. These data are consistent with earlier reports showing the effects of boron on lipid metabolism-related genes [ 21 , 39 ]. For example, Kucukkurt et al showed that 10 mg/kg B (as BA) increased PPARγ expression in the liver in HFD-fed rats [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…These data are consistent with earlier reports showing the effects of boron on lipid metabolism-related genes [ 21 , 39 ]. For example, Kucukkurt et al showed that 10 mg/kg B (as BA) increased PPARγ expression in the liver in HFD-fed rats [ 39 ]. On the other hand, supplemental BA (30 mg/L B) in drinking water decreased the PPARγ in the liver [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In a recent study, it was concluded that boron supplements affect lipid metabolism as a result of the relationship between total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride levels in rats fed a high-fat diet [36]. In our study, except for an important decrease in the H-BA group, the other study groups did not affect serum CHOL levels in aged rats.…”
Section: Discussioncontrasting
confidence: 48%
“…In a study conducted by İnce and colleagues in rats with gentamicin-induced renal damage, it was observed that boron supplementation led to reduced expressions of TNF-α, NFκB, IL-1β, and IFN-γ mRNAs in the kidneys (20). Kucukkurt et al showed that boron decreased IL1-β and TNF-α gene expression levels in a dose-dependent manner in high-fat fed rats (21).…”
Section: Discussionmentioning
confidence: 99%